2009
DOI: 10.1016/j.jaapos.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Welch Allyn SureSight for measurement of magnitude of astigmatism in 3- to 7-year-old children

Abstract: Purpose-To evaluate the accuracy of the Welch Allyn SureSight in noncycloplegic measurements of astigmatism as compared to cycloplegic Retinomax K+ autorefractor measurements of astigmatism in children from a Native American population with a high prevalence of high astigmatism.Methods-Data are reported for 825 3-to 7-year-old children with no ocular abnormalities. Each child had a Retinomax K+ cycloplegic measurement of right eye astigmatism with a confidence rating ≥8 and 3 attempts to obtain a SureSight mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
2
22
0
2
Order By: Relevance
“…Positive likelihood ratios describe how many more times a “refer” result is likely to be observed in children with the target disorders than in unaffected children. 37 The positive likelihood ratio of 7.7 for a “refer” outcome by the PVS was significantly higher than that for the Sure Sight Autorefractor and represents a moderate, but not conclusive, increase in the likelihood that the child has strabismus or amblyopia. The positive likelihood ratio of 1.9 for the SureSight Autorefractor denotes only a minimal increase in the likelihood that the child has one of these conditions.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Positive likelihood ratios describe how many more times a “refer” result is likely to be observed in children with the target disorders than in unaffected children. 37 The positive likelihood ratio of 7.7 for a “refer” outcome by the PVS was significantly higher than that for the Sure Sight Autorefractor and represents a moderate, but not conclusive, increase in the likelihood that the child has strabismus or amblyopia. The positive likelihood ratio of 1.9 for the SureSight Autorefractor denotes only a minimal increase in the likelihood that the child has one of these conditions.…”
Section: Resultsmentioning
confidence: 92%
“…Negative likelihood ratios describe how many fewer times a “pass” result is likely to be observed in children with the target disorders than in unaffected children. 37 The negative likelihood ratio of 0.03 for the PVS was significantly lower than that for the SureSight Autorefractor and represents the low probability that a child with the targeted condition of strabismus or amblyopia will receive a “pass” outcome (ie, affected children have a high probability of being correctly identified by the PVS device).The negative likelihood ratio of 0.42 for the SureSight Autorefractor reflects a moderate probability that children affected by the targeted conditions will be missed by SureSight Autorefractor screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Other researches also have indicated that the Retinomax and the SureSight provided valid measures of refractive error in young children. 48 However, data on their intra-tester or inter-tester agreement are scarce. A few, small-sample studies evaluated the intra-tester (i.e., test-retest) agreement of the two instruments in a variety of age groups, 9–14 and results suggested good intra-tester agreement for both instruments in the preschool age group (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the Retinomax and the SureSight for identifying vision disorders has been well established, 48 and these instruments are already used in vision screening and clinical practice by clinicians, nurses and lay screeners. A few studies 9–14 have investigated the intra-tester agreement (i.e.…”
mentioning
confidence: 99%